Prevalence of malnutrition and its associated factors among 18,503 Chinese children aged 3–14 years - Zhang, Xiaoqian; Wang, Qiong; Gao, Ziyu; Zhang, Zifeng; Wu, Jing; Zhang, Zhixin; Niu, Wenquan (Frontiers in Nutrition, 2023)
Background Child malnutrition places a major burden on global public health. We aimed to estimate the prevalence of child malnutrition and identify its potential factors among children aged 3–14 years from Beijing and Tangshan. Methods We cross-sectionally recruited 18,503 children aged 3–14 years from September 2020 to January 2022, according to a stratified cluster random sampling strategy. Child malnutrition was defined according to the World Health Organization criteria. Data were analyzed by STATA software and R language. Results The prevalence of malnutrition among 18,503 children was 10.93%. After multivariable adjustment, seven factors significantly associated with child malnutrition were parental education (adjusted odds ratio, 95% confidence interval, p: 1.52, 1.40 to 1.67, <0.001), family income (1.23, 1.16 to 1.30, <0.001), fast food intake frequency (1.14, 1.06 to 1.21, <0.001), night meals intake frequency (1.09, 1.04 to 1.15, <0.001), eating speed (1.01, 1.01 to 1.02, <0.001), maternal obesity (0.97, 0.95 to 0.99, <0.001), and paternal obesity (0.97, 0.96 to 0.98, <0.001). The seven significant factors had better prediction performance (area under the receiver operating characteristic, 0.956) for child malnutrition. Conclusion Approximately 10% of Chinese children aged 3–14 years were in malnutrition status, and seven factors were found to be significant predictors for child malnutrition.